Enhanced seed quality of late sown wheat (Triticum aestivum) at stress temperature via safe limits of seed hydro-priming - BASSI, GEETA; TONDON, AMBALIKA; RANDHAWA, H S (The Indian Journal of Agricultural Sciences, 2015)
Seed priming is an important physiological seed quality enhancement method. It provides a low-cost practical solution to seed germination under stress conditions. Abiotic stresses like low temperature and inadequate moisture during sowing season, many a times result in poor germination and poor plant stand leading to drop in crop yield. To harvest the full genetic potential, seeds must germinate and seedlings emerge quickly and uniformly throughout the field so that light, water and other soil nutrients may be utilized with maximum efficiency. However, this does not always happen in nature. In Punjab during sowing, prevailing low temperature, closure of canals or scanty rains result in poor germination and poor crop stand of late sown wheat. Therefore, keeping in view the prospects of this technique, the present investigations were undertaken to standardize the safe time limit of seed hydration and to register its effect on different physiological and molecular parameters in late sown wheat (Triticum aestivum L.) variety PBW 509. Different hydration durations applied were 8 to 10hr, 12 to 14hr, 14 to 16 hr and 16 to 18 hr. The results revealed that hydration for 16 to18hr enhanced the seed quality parameters in terms of seed germination, emergence and seed vigour, Activity of hydrolyzing enzymes was elevated during initial 48hr of its germination. It is due to the efficient production and utilization of germination metabolites and better genetic repair.